(untitled) (Al-Qamar, 2021)
The present study emphases on investigating the etiology of women’s association in crimes and its belongings on their personal relations as well family members and kids during sentence. Each crime on the world adds in grief, and negative affect to the world, either it is committed by male or female. In Muslim community like Pakistan, that crime might be thought of female crimes goes past human observation as females are seen as pure and accommodating creature of God; loaded with adoration and joy. This investigation contrariwise features the horrendous side of female criminality in Pakistani society of Punjab Pakistan; particularly studying the cases of those females who were convicted of murder that is strictly forbidden in Islam. The present research proposed to clarify that socio-economic and cultural factors i.e., Islamic society, low level of education, less implication of religious values, economically dependency and patriarchal system are the dragging factors which are forced the women to obligate crimes in Pakistan. The study depicts how anger builds up in innocent women with Islamic and religious values and no criminal background which has led them to commit such cold-blooded murders. The in-hand research was grounded on the in-depth conversations conducted by the researcher herself from female convicted of murderers from five major jails of Islamic republic Punjab, Pakistan where ten imprisoned women were randomly selected for in profundity interviews from respectively jail and overall, 50 ladies were interviewed during the period of research. Case studies were established on each individual case and results were drawn through thematic analysis which confirmed that majority of the respondents were Muslims and have committed crime due to shortage of economic resources, absence of education, early marriage, bride exchange, less implication of Islamic values, illegal relationships and undesirable affairs with others that developed disorders in the females out of which frustration they were committed such stern felony.